2019
DOI: 10.3390/geosciences9120510
|View full text |Cite
|
Sign up to set email alerts
|

A Silicified Carboniferous Lycopsid Forest in the Colorado Rocky Mountains, USA

Abstract: The 1930 discovery of Carboniferous lycopsid fossils in south central Colorado resulted in the naming of a new species of scale tree, Lepidodendron johnsonii (=Lepidophloios johnsonii (Arnold) DiMichele). Cellular structures of L. johnsonii axes and periderm are preserved in silica—an unusual mode of fossil preservation for Pennsylvanian lycopsid plant remains. The early reports on the Trout Creek lycopsid fossils focused on taxonomic and paleobotanical aspects. Our 2019 reinvestigation of the locality produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Recent studies about this subject found that silica may be in the form of opal-A, opal-CT (chalcedony-tridymite) and quartz, respectively, during diagenesis in aqueous sediments (Mustoe, 2017;Viney et al, 2019). It is a common belief that silicification occurs in this order in fossilized wood, but in many studies the fossilization of woods may involve multiple phases of mineralization.…”
Section: Optical Microscope Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies about this subject found that silica may be in the form of opal-A, opal-CT (chalcedony-tridymite) and quartz, respectively, during diagenesis in aqueous sediments (Mustoe, 2017;Viney et al, 2019). It is a common belief that silicification occurs in this order in fossilized wood, but in many studies the fossilization of woods may involve multiple phases of mineralization.…”
Section: Optical Microscope Investigationsmentioning
confidence: 99%
“…Petrified wood is a fossil formed due to burial of trees by sediments in areas close to volcanic activity and is an important resource for understanding biodiversity and paleogeography. The petrification of wood occurs in the form of replacement of organic parts by inorganic materials in waters affected by volcanism or the permineralization of inorganic material in tissues (Mustoe, 2017;Mustoe and Viney, 2017;Viney et al, 2019). During the silicification process, organic substances in the tissues of the tree are removed and are replaced by silica and/or some other elements (Ca, Cu, Fe etc.).…”
Section: Introductionmentioning
confidence: 99%